Economic Evaluation of Tourism for Natural Areas: Development of a Toolkit Approach - Wood, David; Glasson, J.; Carlsen, Jack; Hopkins, Diane (Sustainable Tourism CRC, 2006)
Please note that only a summary of the report in draft form is available through espace. The full report can be purchased at www.crctourism.com.au through the bookshop.PREFACEThis study seeks to provide simple methods to evaluate the contribution of natural area tourism to local/regional economies. It draws on work undertaken in 2003 by Carlsen and Wood (see Carlsen & Wood 2004) and longitudinal research undertaken by Wood in the Gascoyne region of Western Australia since 1997 (Wood & Dowling 2002; Wood 2003). The former study assessed the economic contribution of tourism to two Western Australian regions (the Gascoyne Coast and Southern Forests), whilst the latter provides stratified samples of tourism data each April in most years since 1997 and data from the other significant tourism seasons collected over two years between 2002 and 2004.Whilst other studies in Australia and abroad have evaluated the economic contribution of natural area tourism to economies, data collection remains an issue for many natural area managers with limited personnel and financial resources. Similarly, the presentation of information suitable for funding decision makers is a vexed issue that sometimes inhibits the successful use of tourism data and interpretive reports. The Department of Conservation and Land Management (CALM) in Western Australia has successfully used the work of Carlsen and Wood to augment management resources in the state's parks. This success is attributable to CALM's mounting of a plausible business case and toits confidence in tourism data collected independently by Wood, as well as Wood and Carlsen over a prolonged period. This prolonged data collection informs the current project providing insights into suitable data collection methods, sample size, key data required to assess economic contributions and methods for analysis and presentation of data.The project was conducted by the Curtin Sustainable Tourism Centre (CSTC), in collaboration with researchers from the University of Queensland, under the auspices of the Sustainable Tourism Cooperative Research Centre (STCRC).